2016
DOI: 10.1002/cssc.201600678
|View full text |Cite
|
Sign up to set email alerts
|

A Fundamental Tandem Mass Spectrometry Study of the Collision‐Activated Dissociation of Small Deprotonated Molecules Related to Lignin

Abstract: The collision-activated fragmentation pathways and reaction mechanisms of 34 deprotonated model compounds representative of lignin degradation products were explored experimentally and computationally. The compounds were evaporated and ionized by using negative-ion mode electrospray ionization doped with NaOH to produce abundant deprotonated molecules. The ions were isolated and subjected to collision-activated dissociation (CAD). Their fragment ions were then isolated and also subjected to CAD. This was repea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…163.0395, error 3.492 ppm) and fragment ion at m/z 119.0491 (C 8 H 7 O) generated by [M‐H‐CO 2 ] – was identified to be coumaric acid, which was identical with the fragmentation regularity of p‐coumaric acid reported by Marcum et al. (2016). Compound 57 was tentatively classified as 7‐(E)‐9‐ketohexadecarbone‐7‐enoic acid or its isomer.…”
Section: Resultssupporting
confidence: 79%
“…163.0395, error 3.492 ppm) and fragment ion at m/z 119.0491 (C 8 H 7 O) generated by [M‐H‐CO 2 ] – was identified to be coumaric acid, which was identical with the fragmentation regularity of p‐coumaric acid reported by Marcum et al. (2016). Compound 57 was tentatively classified as 7‐(E)‐9‐ketohexadecarbone‐7‐enoic acid or its isomer.…”
Section: Resultssupporting
confidence: 79%
“…7 In addition, collision activated dissociation studies performed on several substituted aryl carboxylic anions have also revealed loss of CO 2 molecules. 8,9 However, the UV electronic excitation of deprotonated benzoic acid proved to be totally inefficient to induce fragmentation of the anion, and the molecular anion remained intact. 10 Remarkably, the opposite happens for the deprotonated naphthoic acid homologue, which exhibits decarboxylative fragmentation due to the opening of a new low-energy channel involving internal conversion and dissociation in the ground state.…”
Section: ■ Introductionmentioning
confidence: 99%
“…They were able to identify and count various oxygen-containing functionalities for their individual analytes (carboxylic acid, hydroxymethyl, acetyl, keto, aldehyde, methoxy, aliphatic hydroxy, and nitro groups) and then applied their method to LC-MS/MS analysis for a mixture of four of the compounds. This proved the applicability of using higher-order MS n analyses to better understand the composition of small lignin-related compounds using even a simple low-resolution, ion trap MS. A follow up study by Marcum et al (2016) continued this study, looking at CID spectra of 34 model lignin degradation products via both experimental and computational approaches. MS/MS experiments up to MS 6 were performed to characterize these fragments and the fragmentation patterns allowed the researchers to clearly distinguish carboxylic acid, aldehyde, ester, and phenol groups.…”
Section: Liquid Chromatography-ms/msmentioning
confidence: 99%
“…Later, Zhu et al expanded on these fundamental approaches by including ion-molecule reactions with diethylmethoxyborane (DEMB) to identify phenol functionalities in deprotonated monomeric and dimeric lignin degradation products via tandem MS. The group began by analyzing model lignin-like compounds containing phenol, carboxylic acid, and other functionalities via negative ESI ionization with an ion trap MS, including NaOH as a dopant (Zhu et al, 2016). All analytes were deprotonated to form [M-H]ions and then allowed to react with DEMB in an external reagent mixing manifold, forming DEMB adduct ions ([M-H + DEMB] -), some also having lost a methanol molecule ([M-H + DEMB-MeOH] -).…”
Section: Liquid Chromatography-ms/msmentioning
confidence: 99%